On the Concept of "Coping Strategies" Behavior - Mirbolok, Amir (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
In modern psychological science, the problem of coping strategies is studied from various angles, according to different activities. Analyzing the problem, it is easy to notice a certain identity of used concepts such as coping reactions, coping strategies and coping behaviors, freely used in literature, where "coping" covers a broad scope, from unconscious psychological defenses to the conscious and deliberate coping with stress and anxiety situations.